Encyclopedia of prisons & correctional facilities - Bosworth, Mary (Gale virtual reference library, 2005)
The two-volume Encyclopedia of Prisons and Correctional Facilities, originally published in print format in 2004, aims to provide a critical overview of penal institutions within a historical and contemporary framework.